The Influence of Exercise with Target Wall Media on Volleyball's Under-Passing Ability in Middle High School Students - Alfiah Rizqi Azizah; Inggar Fadillah; Ari Susanto (JUMORA: Jurnal Moderasi Olahraga, 2022)
The purpose of this study was to improve the ability to pass down volleyball with the target wall media. This type of research is an experimental study with lower passing exercises using a target wall using circles and ropes on the lower passing ability of the students. The research subjects were volleyball extracurricular students in middle-high school; all students are 20 children. Based on the results of the calculation of the first hypothesis test, it is known that there is an effect of bottom passing practice using a target wall using a rope on the ability to pass down. The results of the calculation of the second hypothesis are known that there was an effect of lower passing practice using a target wall by using a circle on the ability to pass down. The results of the average comparison are known that the lower passing practice using the target wall using a circle is better than the under-passing exercise using the target wall using a rope on the volleyball bottom passing ability. The results of the comparison of the two training methods concluded that the lower passing exercise using a target wall using a circle had better results compared to the lower passing practice using a target wall using a rope on the volleyball bottom passing ability of the students. Keywords: bottom passing practice, target wall using circle and rope